A place for us : a novel - Mirza, Fatima Farheen, 1991- (SJP for Hogarth, 2018)
As an Indian wedding gathers a family back together, parents Rafiq and Layla must reckon with the choices their children have made. There is Hadia: their headstrong, eldest daughter, whose marriage is a match of love and not tradition. Huda, the middle child, determined to follow in her sister<U+2019>s footsteps. And lastly, their estranged son, Amar, who returns to the family fold for the first time in three years to take his place as brother of the bride. What secrets and betrayals have caused this close-knit family to fracture? Can Amar find his way back to the people who know and love him best?